Planʺ Sorokskoĭ bukhty po opisi otdi︠e︡lʹnoĭ sʺëmki Bi︠e︡lago mori︠a︡ vʺ 1887 i 88 g.g. / Izdanʺ vʺ Gl. Gidrograf. Upr. M-go M-stva vʺ 1890 g. - Russia. Glavnoe gidrograficheskoe upravlenīe (Sankt-Peterburg : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; [Санкт-Петербург] : Морское министерство, Главное гидрографическое управленіе, 1890)
Depths shown by soundings and isolines.; Main title translation: Plan of Sorokskaya Bay according to the surveys of the White Sea of 1887 and 1888.; Top margin title translation: White Sea, Onega Bay.; Greenwich meridian.; Includes note.; "No. 372" -- bottom left margin Grayscale; 1:40,000